2010
DOI: 10.1007/s00268-010-0599-9
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Contusion: An Update on Recent Advances in Clinical Management

Abstract: Pulmonary contusion is a common finding after blunt chest trauma. The physiologic consequences of alveolar hemorrhage and pulmonary parenchymal destruction typically manifest themselves within hours of injury and usually resolve within approximately 7 days. Clinical symptoms, including respiratory distress with hypoxemia and hypercarbia, peak at about 72 h after injury. The timely diagnosis of pulmonary contusion requires a high degree of clinical suspicion when a patient presents with trauma caused by an appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
133
0
15

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(154 citation statements)
references
References 181 publications
6
133
0
15
Order By: Relevance
“…10,37 Furthermore, extrapulmonary traumatic injury (eg, sinonasal or oropharyngeal cavities) can lead to aspiration of blood, which also gives the appearance of lung hemorrhage. 20,38 Interestingly, external injuries consistent with traumatic injury (eg, fractures) were detected in the majority of the bats diagnosed with pulmonary barotrauma.…”
Section: Discussionmentioning
confidence: 99%
“…10,37 Furthermore, extrapulmonary traumatic injury (eg, sinonasal or oropharyngeal cavities) can lead to aspiration of blood, which also gives the appearance of lung hemorrhage. 20,38 Interestingly, external injuries consistent with traumatic injury (eg, fractures) were detected in the majority of the bats diagnosed with pulmonary barotrauma.…”
Section: Discussionmentioning
confidence: 99%
“…52,57,58 As an example, the pathologic evolution of pulmonary contusion (itself a risk factor for pneumonia) typically reaches peak pulmonary decompensation at ϳ72 h postinjury. 59 Another issue is that the results of VAE monitoring will differ depending on whether data are collected electronically or manually and particularly on the intensity of electronic data capture. 52 More importantly, retrospective studies suggest that VAP prevention bundles do not affect the incidence of VAE.…”
Section: Initial Studies On Ventilator-associated Event Surveillancementioning
confidence: 99%
“…Some studies have also reported that up to 20% of patients with blunt chest trauma developed acute lung injury (ALI) or acute respiratory distress syndrome (ARDS) (14,15). Also, airway obstruction, tension pneumothorax, and massive hemoth- orax are the immediate, life-threatening complications of chest trauma that require evaluation and treatment during primary survey (16).…”
Section: Introductionmentioning
confidence: 99%
“…Thoracic injuries cover the spectrum from trivial to lethal, and more than half of them are associated with head, abdomen, or extremity trauma (6,15). Therefore, proper evaluation of thoracic injury complications could prevent delayed treatment consequences and reduce mortality and morbidity rates (17,18).…”
Section: Introductionmentioning
confidence: 99%